Waste to wealth: production of activated carbon from agricultural waste - Abdul Aziz, Nor Izzah; Othman, Norzila; Yunus, Zalilah Murni (Penerbit UTHM, 2020)
Adsorption is the main process for wastewater and drinking water treatment. The ability of activated carbon as an absorbent was proven by many researchers. Agriculture waste can be produced as an activated carbon based on availability, cost, and purity. Physical and chemical activations are the main process in activated carbon (AC) development. Both processes have its own advantage. Before proceeding with the activation process the precursor must be characterized for metal element and surface functional group by doing (X-Ray Fluorescence) XRF and Fourier transform infrared (FTIR). TGA will determine the exact carbonization temperature. Adsorbent pore will be analyzed using BET. Activating agent and carbonization temperature gives the main effect for surface area and total pore volume of AC. This chapter will review the AC development process and the exact characterization method in preparing the AC.